Analysis of Vegetative Growth of Tobacco Plants (Nicotiana tabacum L) Using Azotobacter and Biohumic Media - Baharuddin, Baharuddin; Rahim, Iradhatullah; Zamzam, Syamsiar; Sumawati, Sumawati; Qadri, Sri Nur (Urecol Journal. Part G: Multidisciplinary Research, 2025)
The dependence of tobacco farmers on synthetic chemical fertilizers for many years has led to a decline in soil quality and crop yields in the long term, One of the main challenges in tobacco production is to produce quality seeds that can optimally support crop productivity. The research method used a random design of a non-factorial group, each treatment consisted of 3 treatments tested, namely 4 combinations of planting media, namely P0 (Control), P1 (Azotobacter), P3 (Biohumic), P4 (Azotobacter+Biohumic). The results obtained in this study showed that the best results in the combination treatment of azotobacter and biohumic consistently gave the best results on all plant growth observation parameters, this shows a significant synergistic effect between nitrogen fixation by azotobacter and increased nutrient availability by biohumic